2020
DOI: 10.3389/fimmu.2020.00731
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan-Dependent Endo-Lysosomal Fusion Affects Intracellular Survival of Salmonella Typhimurium in Epithelial Cells

Abstract: Proteoglycans (PGs) are glycoconjugates which are predominately expressed on cell surfaces and consist of glycosaminoglycans (GAGs) linked to a core protein. An initial step of GAGs assembly is governed by the β-D-xylosyltransferase enzymes encoded in mammals by the XylT1/XylT2 genes. PGs are essential for the interaction of a cell with other cells as well as with the extracellular matrix. A number of studies highlighted a role of PGs in bacterial adhesion, invasion, and immune response. In this work, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Surprisingly, the expression of the barrier proteins occludin, claudin-1, claudin-2, claudin-7, and EpCAM was not significantly influenced by S. Typhimurium SL1344, as was reported by Sun et al ( 40 ). According to previous research, Salmonella usually breaks through intestinal epithelial cells to the lamina propria of the mucosa via transcytosis of M cells, epithelial endocytosis, and phagocyte uptake ( 41 43 ). In the colon, virulence proteins from Salmonella interact with ordinary intestinal epithelial cells and rearrange the cytoskeleton ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the expression of the barrier proteins occludin, claudin-1, claudin-2, claudin-7, and EpCAM was not significantly influenced by S. Typhimurium SL1344, as was reported by Sun et al ( 40 ). According to previous research, Salmonella usually breaks through intestinal epithelial cells to the lamina propria of the mucosa via transcytosis of M cells, epithelial endocytosis, and phagocyte uptake ( 41 43 ). In the colon, virulence proteins from Salmonella interact with ordinary intestinal epithelial cells and rearrange the cytoskeleton ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reporters in the bacterial cytosol, FPs expressed by DFR are less likely to be affected by pH changes due to the pH homeostasis in the bacterial cytosol. However, extreme external conditions such as presence in phagolysosome of host cells can result in acid shock and override pH homeostasis, as determined by DFR with an acid shock‐induced promoter (Galeev et al., 2020). Although drop of cytosolic pH will be transient due to compensation by acid shock response, pH‐mediated effects on FP signal intensities should be considered in interpretation of results.…”
Section: Generation Of Fp Reportersmentioning
confidence: 99%
“…A component of balancing the response occurs in the 3rd trimester through allergen aggregated with IgG transported across the placenta which down-regulates sensitization through inhibitory IgG receptors. This being the case, high maternal intake of milk would increase IgG antibodies complexed with milk and when transported across the placenta could reduce the risk of CMA ( 23 ). Balancing the Th-1 and Th-2 responses after delivery is affected by a rapidly diversifying ecological balance of organisms (microbiome) on the infant’s skin, in the respiratory and gastrointestinal tracts.…”
Section: The Ontogeny Of Cma and The Allergic Marchmentioning
confidence: 99%
“…In animal models, it has been shown that antigen-immunoglobulin (IgG) immune complexes from sensitized dams were transferred to the newborn through the neonatal Fc receptor resulting in the induction of antigen-specific FoxP3(+) CD25(+) regulatory T cells ( 43 ). The transfer of these immune complexes could induce tolerance and support the development of primary prevention of CMA ( 23 , 44 ).…”
Section: Primary Prevention Of Cmamentioning
confidence: 99%